Vasodilator-stimulated phosphoprotein restricts cell-to-cell spread of Shigella flexneri at the cell periphery - Lee, Soo Young (Microbiology (Reading), 2015)
Shigella spp. are intracellular bacterial pathogens that cause diarrhoeal disease in humans. Shigella utilize the host actin cytoskeleton to enter cells, move through the cytoplasm of cells and pass into adjacent cells. Ena/VASP family proteins are highly conserved proteins that participate in actin-dependent dynamic cellular processes. We tested whether Ena/VASP family members VASP (vasodilator-stimulated phosphoprotein), Mena (mammalian-enabled) or EVL (Ena-VASP-like) contribute to Shigella flexneri spread through cell monolayers. VASP and EVL restricted cell-to-cell spread without significantly altering actin-based motility, whereas Mena had no effect on these processes. Phosphorylation of VASP on Ser153, Ser235 and Thr274 regulated its subcellular distribution and function. VASP derivatives that lack the Ena/VASP homology 1 (EVH1) domain or contain a phosphoablative mutation of Ser153 were defective in restricting S. flexneri spread, indicating that the EVH1 domain and phosphorylation on Ser153 are required for this process. The EVH1 domain and Ser153 of VASP were required for VASP localization to focal adhesions, and localization of VASP to focal adhesions and/or the leading edge was required for restriction of spread. The contribution of the EVH1 domain was from both the donor and the recipient cell, whereas the contribution of Ser153 phosphorylation was only from the donor cell. Thus, unlike host proteins characterized in Shigella pathogenesis that promote bacterial spread, VASP and EVL function to limit it. The ability of VASP and EVL to limit spread highlights the critical role of focal adhesion complexes and/or the leading edge in bacterial passage between cells.